Selected Factors Related To Anhedonia Among Persons With Major Depressive Disorder, Southern Region - อาแว, วนิดา; อุปเสน, รัชนีกร (Journal of The Royal Thai Army Nurses, 2018)
The purposes of this research were to examine level of anhedonia of persons with major depressive disorder and to study the relationship between gender, age, obsessive-compulsive symptoms, depression, social functioning, anxiety, stressfull life event and anhedonia among persons with major depressive disorder. The samples were 144 MDD patients, randomly selected by purposive sampling technique. The research instruments were: 1) personal factor 2) obsessive- compulsive symptoms 3) depression 4) anxiety 5) life event stress 6) social functioning and 7) Temporal experience of pleasure scale (TEPS). All instruments were verified for Content Validity Index by five experts and reliability >.80 (0.98, 0.94, 0.85, 0.95, 0.83,0.92). Data were analyzed by using descriptive statistics, Chi-square and Point Biserial Correlation. 1. Participants had the anhedonia about 62.5% (x = 3.52, S.D. = 1.03) 2. Age was significant correlation with anhedonia (rpb =.163) 3. Obsessive-compulsive symptom, depression, anxiety and life event stress were positively significant correlation with anhedonia (rpb = .382, rpb = .444, rpb = .294, rpb = .294 respectively) 4. social functioning was negatively significant correlation with anhedonia (rpb = -.470) 5. gender was not related to anhedonia among persons with Major Depressive disorder.